Southern Hemisphere atmospheric blocking in CMIP5 and future changes in the Australia‐New Zealand sector - Patterson, M; Bracegirdle, T; Woollings, T (American Geophysical Union, 2019)
Many general circulation models (GCMs) fail to capture the observed frequency of atmospheric blocking events in the Northern Hemisphere, however few studies have examined models in the Southern Hemisphere (SH) and those studies that have, have often been based on only a few models. To provide a comprehensive view of how the current generation of coupled GCMs perform in the SH and how blocking frequency changes under enhanced greenhouse gas forcing, we examine the output of 23 models from the Coupled Model Intercomparison Project Phase 5. We find that models have differing biases during winter, when blocking occurrence is highest, though models underestimate blocking frequency south of Australia during summer. We show that models generally have a reduction in blocking frequency with future anthropogenic forcing, particularly in the Australia‐New Zealand sector with the number of winter blocked days reduced by about one third by the end of the 21st century.